2012
DOI: 10.1111/j.1539-6924.2012.01896.x
|View full text |Cite
|
Sign up to set email alerts
|

Revisions of the Fish Invasiveness Screening Kit (FISK) for its Application in Warmer Climatic Zones, with Particular Reference to Peninsular Florida

Abstract: The initial version (v1) of the Fish Invasiveness Scoring Kit (FISK) was adapted from the Weed Risk Assessment of Pheloung, Williams, and Halloy to assess the potential invasiveness of nonnative freshwater fishes in the United Kingdom. Published applications of FISK v1 have been primarily in temperate-zone countries (Belgium, Belarus, and Japan), so the specificity of this screening tool to that climatic zone was not noted until attempts were made to apply it in peninsular Florida. To remedy this shortcoming, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 33 publications
2
66
0
2
Order By: Relevance
“…The present study aims to determine which non‐native fish species are likely to pose a high risk of being invasive for the River Neretva catchment and for similar ecosystems of the Adriatic and Mediterranean regions. Another objective was to compare two decision support tools (available at http://www.cefas.co.uk/nns/tools/), namely, FISK v2 (Lawson et al ., ) and the Aquatic Species Invasiveness Screening Kit (AS‐ISK: Copp et al , ), which was recently developed to replace the taxon‐specific toolkits of the FISK family (Copp, ). Similar to FISK v2, AS‐ISK can be applied in virtually any climatic zone.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…The present study aims to determine which non‐native fish species are likely to pose a high risk of being invasive for the River Neretva catchment and for similar ecosystems of the Adriatic and Mediterranean regions. Another objective was to compare two decision support tools (available at http://www.cefas.co.uk/nns/tools/), namely, FISK v2 (Lawson et al ., ) and the Aquatic Species Invasiveness Screening Kit (AS‐ISK: Copp et al , ), which was recently developed to replace the taxon‐specific toolkits of the FISK family (Copp, ). Similar to FISK v2, AS‐ISK can be applied in virtually any climatic zone.…”
Section: Introductionsupporting
confidence: 75%
“…Risk analysis of non‐native fish species in inland waters of the Mediterranean Region and adjacent areas has so far involved only risk identification (screening), which has employed the Freshwater Fish Invasiveness Screening Kit (FISK: Copp et al , , ; Lawson et al , ). In its application to the Balkans Region (Simonović et al , ), a high rate of fish translocations into newly constructed reservoirs was reported, and this was the likely cause of the relatively low threshold FISK score achieved (Copp, ), which distinguishes between ‘medium‐risk’ and ‘high‐risk’ species, compared with areas with a similar level of endemism, namely, the Iberian Peninsula (threshold = 20.25: Almeida et al , ) and Turkey (threshold = 23: Tarkan et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Assessments were carried out by a single assessor (N.P.) using the calibrated version of the FISK (v2.03), which is freely available for download (Lawson et al, 2012). The critical thresholds for categorising fish species as low, medium or high risk of being invasive have been calibrated by Copp et al (2009), whereby scores <1 indicate low risk, scores of 1 to 18.9 indicate medium risk, and scores of 19 (to a maximum of 54) indicate high risk.…”
Section: Methodsmentioning
confidence: 99%
“…Assessments using ENSARS begin with the Pre‐screening module (Copp, Russell, et al, ), which originally comprised a suite of taxon‐specific toolkits and a generic screening module. Since ENSARS’ creation, the generic screening module was combined with the architecture of version 2 (Lawson, Vilizzi, Hill, Hardin, & Copp, ) of the Fish Invasiveness Screening Kit (FISK: Copp et al, ; Vilizzi et al, ) to create the Aquatic Species Invasiveness Screening Kit (AS‐ISK: Copp, Vilizzi, et al, ). The schemes upon which ENSARS was based (cited here above) have been slightly modified, and the AS‐ISK was developed, to comply with the “minimum standards” (Roy et al, ) for evaluating NN species risks under Council Regulation No 1143/2014 on the prevention and management of alien invasive species (EU, ).…”
Section: Methodsmentioning
confidence: 99%